Territorial Structure оf Professional Football in the North Caucasus federal District - I. P. Suprunchuk (Наука. Инновации. Технологии, 2023)
Introduction. The article examines the territorial structure of football on the territory of the North Caucasus Federal District. Spatial analysis of the functioning of professional football clubs has shown the presence of several periods of football development in the region. At the present stage, the territorial structure is narrowed, the professional level of football has been preserved only in the regional capitals and cities of the Caucasian Mineral Waters. Two types of intraregional territorial structure of football are distinguished. The monocentric type is characteristic of Chechnya, Ingushetia and Karachay-Cherkessia. During the transformation, the monocentric structure also became in Kabardino-Balkaria, North Ossetia and Dagestan. Stavropol Krai is characterized by a polycentric territorial structure.Materials and research method. In the course of the study, a spatial analysis of the development of professional football clubs was carried out, methods of comparative geographical and historical geographical description and analysis were used.Research results and their discussion. Four stages in the development of the territorial structure of football in the NCFD have been identified. At the moment, there is a reduction in the number of professional football clubs and a contraction of their territorial network. This reduction occurred sequentially. The large number of clubs in the region in the early 1990s is explained by the transition from the Soviet football hierarchy and the rise of semi-professional clubs in the Russian football league system. In 1994, there was a sharp decline in the number of football clubs in the region. By the end of the 1990s, the football network was recovering and growing. A new decline occurred in the second half of the 2000s. After a short period of stability in 2014, the maximum compression of the network occurs. To date, the number of clubs has grown slightly.Conclusions. Professional football in the NCFD has gone through different periods in its development and has experienced a transformation – from a deep underdeveloped periphery in the Soviet period through expansion and development in the 2000s to compression and simplification in modern times. There are four periods in the change of the territorial structure of professional football in the region, each of which had its own characteristics and the main centers of the region. At the moment, the territorial structure of football is narrowed, it has been preserved only in the regional capitals and cities of the CMW, which was primarily due to economic reasons. Two types of intraregional territorial structure are distinguished – monocentric and polycentric. The main centers of the territorial structure of football in the region are regional capitals.